2014
DOI: 10.4236/gep.2014.24002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal (AM) Fungi on the Physiological Performance of Phaseolus vulgaris Grown under Crude Oil Contaminated Soil

Abstract: An experiment was conducted to assess the influence of arbuscular mycorrhizal (AM) fungi on the performance of Phaseolus vulgaris under crude oil contaminated soil. P. vulgaris was grown on soil under 2%, 4% and 8% (v/w) crude oil contamination. The experimental units were biostimulated with 2 g NPK fertilizer pot −1 and were inoculated with 12 g AM inoculum pot −1. Non inoculated pots served as control. The results showed that AM inoculated pots recorded higher and significantly (P < 0.05) different dry matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
3
5
0
Order By: Relevance
“…The extent of root colonization by mycorrhiza decreased with increasing concentration of crude oil in the soil. The finding of this study corroborates previous report by Nwoko et al (2014) where they observed reduced root colonization by arbuscular mycorrhiza in crude oil contaminated soil. However during the second pot trial, the level of root colonization by mycorrhiza increase with improved crude oil degradation in the contaminated soil.…”
Section: Discussionsupporting
confidence: 93%
“…The extent of root colonization by mycorrhiza decreased with increasing concentration of crude oil in the soil. The finding of this study corroborates previous report by Nwoko et al (2014) where they observed reduced root colonization by arbuscular mycorrhiza in crude oil contaminated soil. However during the second pot trial, the level of root colonization by mycorrhiza increase with improved crude oil degradation in the contaminated soil.…”
Section: Discussionsupporting
confidence: 93%
“…Firstly, our results showed that the addition of AMF inoculum, rhamnolipids, native microbiota, and S. wittichii RW1 to PCCD/F-aged contaminated soil has a positive effect on alfalfa aerial growth and chlorophyll content compared to alfalfa without amendment. These results were expected and are in agreement with several previous studies, which showed that AMF increase plant development in contaminated soils by improving mineral uptake of P, Mn, K, Cu, and Fe [24,41,42]. Thus, it has already been shown that the introduction of rhamnolipids in PAH-polluted soil increased the permeability of ryegrass root cells, which may also increase the nutrient uptake [43].…”
Section: Discussionsupporting
confidence: 91%
“…The effect of pH on the MnP activity was studied at different pH values (3)(4)(5)(6)(7). In brief, the MnP was pre-incubated in 50 mM malonic acid buffer (pH 2.0-5.5) and 50 mM potassium phosphate buffer (pH 6.0-7.0) of different pH values in the range of 3-8 for 24 h at 30 C. Aer incubation, the residual enzyme activity was determined under standard assay conditions.…”
Section: Effect Of Ph and Temperature On The Activity Of Mnpmentioning
confidence: 99%
“…1 The hydrophobic and tenacious nature of polycyclic aromatic hydrocarbons (PAHs) causes them to alter the biological and physicochemical properties of soil, such as the microbial population, soil enzyme activities, water holding capacity, and soil organic matter. 2,3 Due to their negative effects on the environment and tendency to migrate into water bodies, there is an urgent desire to be able to remove PAHs from soil. 4 Physico-chemical methods for the removal of PAHs are highly efficient but they change the soil structure, reduce the soil microbial population and lead to the depletion of nutrients that are essential for plant vegetation.…”
Section: Introductionmentioning
confidence: 99%